Beta-Trace Protein as a Potential Marker of Acute Kidney Injury: A Pilot Study - Katrien Leyssens; Niels Van Regenmortel; Ella Roelant; Khadija Guerti; Marie Madeleine Couttenye; Philippe G. Jorens; Walter Verbrugghe; Amaryllis H. Van Craenenbroeck (Karger Publishers, 2021)
Introduction: Acute kidney injury (AKI) is a frequent complication among patients in the intensive care unit (ICU). The limitations of serum Cr (sCr) in timely detecting AKI are well known. Beta-trace protein (BTP) is emerging as a novel endogenous glomerular filtration rate marker. The aim of this study was to explore the role of BTP as a marker of AKI. Methods: Patients admitted to the ICU undergoing surgery were included. BTP, sCr, Cystatin C (CysC), and neutrophil gelatinase-associated lipocalin (NGAL) were measured preoperatively, postoperatively (post-op), and at the first (D1) and second (D2) post-op day. AKI was defined as an increase of sCr to ≥1.5-fold from baseline within 2 days after surgery. Results: Of the 52 patients studied, 10 patients (19%) developed AKI. Patients with AKI were older (69.6 ± 10.7 vs. 58.1 ± 16.7 years, p = 0.043) and had a longer length of ICU stay (13 [IQR 6-49] vs. 6 [IQR 5-8] days, p = 0.032). Between the 2 groups, the evolution of BTP, sCr, CysC, and NGAL over time differed significantly, with overall higher values in the AKI group. ROC analysis for the detection of AKI within 2 days after surgery showed a great accuracy for BTP. The area under the curve (AUC) for BTP post-op; D1; and D2 was, respectively, 0.869 ± 0.049; 0.938 ± 0.035; and 0.943 ± 0.032. The discriminative power of a BTP measurement on D1 was superior in detecting AKI compared to NGAL (adjusted p value = 0.027). We could not detect a significant difference between the AUCs of other biomarkers (NGAL, sCr, and CysC). Conclusion: Serum BTP is a promising marker for diagnosing AKI in ICU patients undergoing surgery.